Germany : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report ;, 2006)
This Report on the Observance of Standards and Codes data module provides an assessment of Germany's macroeconomic statistics against the Special Data Dissemination Standard (SDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Germany is currently in observance of the SDDS. It meets the SDDS specifications for coverage, periodicity, and timeliness for all data categories. The SDDS data categories are disseminated on Germany's National Summary Data Page, which is hyperlinked on the Dissemination Standards Bulletin Board, and is updated on a timely basis.